Soft Skill Values in Basic Accounting Learning in Accounting Department of Vocational High Schools - Suranto, Suranto; Ristiny, Ristiny; Amanda, Bunga; Mustofa, Rochman Hadi; Gano-an, Jonathan Camana (Edunesia : Jurnal Ilmiah Pendidikan, 2023)
This study aims to describe: (1) soft skill values instilled in students by accounting teachers, (2) the process of instilling soft skills in students by accounting teachers, (3) Barriers and supporting factors in instilling soft skills in students. This research is qualitative using ethnographic design. Data sources of the study are accounting teachers and first-grade students in the accounting department. Data collection techniques were performed through observation, interviews, and documentation. The data analysis technique conducted during the study was analyzing the data contained in the research site in which the results were used as conclusions to answer the objectives of the study. The research results revealed seven aspects of soft skills, namely self-confidence, communication skill, emotional intelligence, critical thinking skill, teamwork ability, time management, and leadership. The instilling of soft skills in students through cooperative learning strategies and providing positive habituation to students was performed during the teaching-learning process. The barriers of instilling soft skills, which are the lack of students’ abilities, the difficulty to control students, and the lack of teachers’ competences in developing learning methods. Whereas, the supporting factors are the small number of students in each class so the instilling of soft skill became sufficient and the numerous supports given by the school community.